2020
DOI: 10.1007/s40843-020-1390-6
|View full text |Cite
|
Sign up to set email alerts
|

The critical role of electrochemically activated adsorbates in neutral OER

Abstract: Developing efficient electrocatalysts for the oxygen evolution reaction (OER) under neutral conditions is important for microbial electrolysis cells (MECs). However, the OER kinetics in neutral electrolytes at present are extremely sluggish, resulting in high overpotentials that greatly limit the energy conversion efficiencies of MECs. Previous studies failed to probe the adsorbates on surface metal sites of catalysts at the atomic scale and elucidate their influence on the catalytic activities, which has impe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Unfortunately, this technique has rarely been applied to study the reconstruction of electrocatalysts. [ 45 ] Due to its extremely high sensitivity, the LEIS requires ultra‐high vacuum conditions and the signal could be blocked by unexpected surface contaminations. Fourier‐transform infrared spectroscopy (FTIR) is conducted by achieving the transitions of vibrational and rotational energy levels from the ground state to the excited state under the continuous change of infrared light.…”
Section: Reconstruction Of Electrocatalystsmentioning
confidence: 99%
“…Unfortunately, this technique has rarely been applied to study the reconstruction of electrocatalysts. [ 45 ] Due to its extremely high sensitivity, the LEIS requires ultra‐high vacuum conditions and the signal could be blocked by unexpected surface contaminations. Fourier‐transform infrared spectroscopy (FTIR) is conducted by achieving the transitions of vibrational and rotational energy levels from the ground state to the excited state under the continuous change of infrared light.…”
Section: Reconstruction Of Electrocatalystsmentioning
confidence: 99%
“…In CV, the morphological evolution was monitored by in situ TEM. [120][121][122] The in situ electrochemical transmission electron microscope support is shown in Figure 7. It consists of a disposable micro-three-electrode battery (electrochemical chip).…”
Section: In Situ Temmentioning
confidence: 99%
“…Unfortunately, these UOR catalysts still exhibit unsatisfactory activity due to the unfavorably strong absorption of the intermediate COO* on Ni 3+ sites [13] . It is reported that the adsorption energy of intermediates was closely related to its electronic structures [14–17] . Thus, regulating the electronic structures of Ni 3+ sites may construct catalytic sites with high UOR intrinsic activity.…”
Section: Figurementioning
confidence: 99%